Changes to Colour Vision on Exposure to High Altitude. Issue 1 (1st March 2011) - Davies, Andrew J.; Morris, DS; Kalson, NS; Wright, AD; Imray, CHE; Hogg, CR
Abstract : Objectives: Several studies have shown deterioration in colour vision at altitudes above 3, 000m. These studies have been conducted in photopic (bright daylight) conditions, whereas many military operations take place in mesopic (dim light) conditions. Data suggests that the tritan colour vision axis (blue cones, TA) are more susceptible to hypoxic insult than protan axis (red cones, PA). The objective of this study was to examine colour vision at high altitude, in mesopic conditions, and using a novel method of assessment to discriminate between the tritan and protan axis. Methods: We examined 42 eyes (21 subjects, mean age 44, range 22-71), at sea level and within 12-36 hours of exposure to 3300m. This was done in a darkened room, with refractive error correction. Colour vision was studied using Chroma Test™, a software programme that analyzes colour contrast threshold (CCT) of both TA and PA. We planned to repeat CCT measurement at 4, 392m, but technology failure prevented this. Non-parametric paired data was examined using the Wilcoxon signed rank test. Results: There was found to be no change to either the PA (p=0.409) or the TA (p=0.871) upon ascent. Within the PA 16 eyes had a lower CCT at high altitude, whilst 26 were higher. In the TA 20 eyes had a lower CCT and 22 were higher. At sea level, mean CCT for PA was 4.21 (SD 2.29) TA was 7.06 (SD 1.77). At 3, 300m mean CCT for PA was 4.36 (SD 2.86) and TA was 6.93 (SD 2.39). Conclusions: This experiment revealed no changes to colour vision with exposure to 3, 300m. This may be below the threshold altitude for cone dysfunction, alternatively colour vision deterioration may be less significant in mesopic conditions.